2017
DOI: 10.1155/2017/1249614
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative Stress‐Related Parthanatos of Circulating Mononuclear Leukocytes in Heart Failure

Abstract: Background. The present study aims to examine the oxidative stress-related activation of poly(ADP-ribose) polymerase (PARP), a cause of parthanatos in circulating mononuclear leukocytes of patients with chronic heart failure (CHF), that was rarely investigated in the human setting yet. Methods. Patients with CHF (n = 20) and age-and body mass index-matched volunteers (n = 15) with a normal heart function were enrolled. C-reactive protein, N-terminal probrain-type natriuretic peptide (pro-BNP), plasma total per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…These effects were more evident in the group with HbA 1c > 6.5%. Furthermore, several studies have demonstrated the importance of leukocytes in the atherosclerotic scenario [82][83][84]. In accordance with these results, an increase in leukocyte-endothelium interactions has been related to oxidative stress in a human model of insulin resistance [85].…”
Section: Discussionsupporting
confidence: 62%
“…These effects were more evident in the group with HbA 1c > 6.5%. Furthermore, several studies have demonstrated the importance of leukocytes in the atherosclerotic scenario [82][83][84]. In accordance with these results, an increase in leukocyte-endothelium interactions has been related to oxidative stress in a human model of insulin resistance [85].…”
Section: Discussionsupporting
confidence: 62%
“…The superfluous activation of PARP-1 can also consume the store of NAD + , exhaust ATP, and destroy the integrity of the oxidative respiratory chain, which leads to cell death by caspase-3-induced necrosis or apoptosis (13). PARP-1 itself, as a substrate of caspase-3, can be decomposed from 116 kDa into 89 and 24 kDa and lose its function (12). In order to prevent the disturbance of caspase-3 in the present study, z-VAD-fmk, an irreversible broad-spectrum inhibitor of the caspase family, was used to pretreat all cells.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive DNA breakage triggered by excessive ROS/RNS production can rapidly activate PARP-1 and result in energy depletion. Notably, the superfluous activation of PARP-1 can also lead to the nucleus releasing a large number of PAR fragments into the cytoplasm, and can translocate apoptosis-inducing factor (AIF), which is another key factor, from the mitochondria to the nucleus in order to induce parthanatos (12). In previous years, numerous studies have identified that parthanatos is involved in the pathogenic mechanisms of neurodegenerative disease, stroke, ischemic reperfusion injury and diabetes mellitus (6,1315), therefore, it may be a novel target for the treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated lipid peroxidation has been shown to be associated with the severity of HF, such as malondialdehyde (MDA) and 4-Hydroxy-2-nonenal (HNE) [68]. In addition, two studies showed a positive correlation between the total plasma peroxide levels (reflecting oxidative stress index) in leukocytes with serum NT-proBNP [8,36]. Mondal et al demonstrated that HF patients with implanted left ventricular assist devices exhibit excessive production of ROS as well as DNA damage in circulating leukocytes [47].…”
Section: Mitochondrial Ros In Pbmcs In Heart Failurementioning
confidence: 99%
“…The 2019 report of the American Heart Association shows that between 2013 and 2016, CVDs, including hypertension, heart failure (HF), coronary heart disease, and stroke, were present in about 48% of patients older than 20 years in the United States [3][4][5]. Significant progress has been made concerning CVD diagnosis and therapies, particularly considering neuro-hormonal modulation, such as natriuretic peptide (NP)-guided therapy [2,[6][7][8][9], but it seems that a plateau has begun to be reached, suggesting new approaches. In this view, since CVDs are generally systemic diseases, an attempt based on circulating cells might be proposed to better understand CVD pathophysiology and to discover new biomarkers.…”
Section: Introductionmentioning
confidence: 99%